Doc's Kingdom - Kramer, Robert; Machover, Robert; MacIsaac, Paul; Gallo, Vincent; Monteiro, Joao César (Cahiers du Cinema Collection, 2010)
Doc lives on the edge of Europe where it imperceptibly slides over into the Third World. As a doctor, he knows that the illness he has contracted ten years before in war-torn Africa is getting worse. The diagnosis is cholera, but Doc knows the disease's real name: despair. His thoughts about his failed struggle for justice and ideals are drowned regularly in alcohol. On the other side of the world lives Jimmy, a speed-loving motorbike freak who, when his mother dies, finds a letter from Doc and discovers that his father, whom he thought was dead, is still alive. The encounter of the two men leads to a reappraisal of two worlds in opposition. [www.amazon.com]